Adding thermal information to multisensory inputs in simulated environments. (3rd February 2010) - Van Doorn, George; Richardson, Barry; Symmons, Mark; Wells, Jonathan
Although simulated environments are improved by adding sensory information, temperature is one input that has rarely featured in them. Here we report findings from experiments that examine the efficacy of adding temperature information to the multimodal complex known to be of benefit in simulations. In the first experiment, Peltier tiles added thermal information to the kinesthetic feedback given by a hand-worn exoskeletal device and this increased ratings for 'presence' during interactions with simulated objects. In an experiment in which exploratory movements across surfaces of differing temperatures were either active or passive-guided, the degree of 'coldness' felt at the fingertip was reported as less intense when movement was active, suggesting that intentionality of movement plays a role in the attenuation of the thermal stimulus. Other work reported here suggests that the perception of temperature is not influenced by a simultaneously presented colour. For example, the perception of coldness is not enhanced when it is processed in conjunction with a blue colour. We discuss the potential value of thermal information within the context of the hypothesis that presence in simulated environments is enhanced by multisensory inputs that include redundant information.